Effect of Empagliflozin on Worsening Heart Failure Events in Patients With Heart Failure and Preserved Ejection Fraction: EMPEROR-Preserved Trial. Issue 16 (19th October 2021) - Packer, Milton; Butler, Javed; Zannad, Faiez; Filippatos, Gerasimos; Ferreira, Joao Pedro; Pocock, Stuart J.; Carson, Peter; Anand, Inder; Doehner, Wolfram; Haass, Markus; Komajda, Michel; Miller, Alan; et al.
Abstract : Background: Empagliflozin reduces the risk of cardiovascular death or hospitalization for heart failure in patients with heart failure with preserved ejection fraction, but additional data are needed about its effect on inpatient and outpatient heart failure events. Methods: We randomly assigned 5988 patients with class II through IV heart failure with an ejection fraction of >40% to double-blind treatment with placebo or empagliflozin (10 mg once daily), in addition to usual therapy, for a median of 26 months. We prospectively collected information on inpatient and outpatient events reflecting worsening heart failure and prespecified their analysis in individual and composite end points. Results: Empagliflozin reduced the combined risk of cardiovascular death, hospitalization for heart failure, or an emergency or urgent heart failure visit requiring intravenous treatment (432 versus 546 patients [empagliflozin versus placebo, respectively]; hazard ratio, 0.77 [95% CI, 0.67–0.87]; P <0.0001). This benefit reached statistical significance at 18 days after randomization. Empagliflozin reduced the total number of heart failure hospitalizations that required intensive care (hazard ratio, 0.71 [95% CI, 0.52–0.96]; P =0.028) and the total number of all hospitalizations that required a vasopressor or positive inotropic drug (hazard ratio, 0.73 [95% CI, 0.55–0.97]; P =0.033). Compared with patients in the placebo group, fewer patients in the empagliflozin group reported outpatient intensification of diuretics (482 versus 610; hazard ratio, 0.76 [95% CI, 0.67–0.86]; P <0.0001), and patients assigned to empagliflozin were 20% to 50% more likely to have a better New York Heart Association functional class, with significant effects at 12 weeks that were maintained for at least 2 years. The benefit on total heart failure hospitalizations was similar in patients with an ejection fraction of >40% to <50% and 50% to <60%, but was attenuated at higher ejection fractions. Conclusions: In patients with heart failure with preserved ejection fraction, empagliflozin produced a meaningful, early, and sustained reduction in the risk and severity of a broad range of inpatient and outpatient worsening heart failure events. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03057977. Abstract : Supplemental Digital Content is available in the text.